2013
DOI: 10.1186/1297-9716-44-40
|View full text |Cite
|
Sign up to set email alerts
|

Differential response of bovine mammary epithelial cells to Staphylococcus aureus or Escherichia coli agonists of the innate immune system

Abstract: Mastitis caused by Escherichia coli and Staphylococcus aureus is a major pathology of dairy cows. To better understand the differential response of the mammary gland to these two pathogens, we stimulated bovine mammary epithelial cells (bMEC) with either E. coli crude lipopolysaccharide (LPS) or with S. aureus culture supernatant (SaS) to compare the transcriptomic profiles of the initial bMEC response. By using HEK 293 reporter cells for pattern recognition receptors, the LPS preparation was found to stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
165
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 177 publications
(184 citation statements)
references
References 84 publications
(134 reference statements)
16
165
1
2
Order By: Relevance
“…They produce various antimicrobial substances and inflammatory mediators that enhance effector functions of innate immunity and stimulate adaptive immunity, playing a pivotal role in the resolution of infection (27). A great number of studies dedicated to the analysis of the defensive response of MEC used killed bacteria or bacterial supernatants; however, those models have a significant limitation, since there is a great difference in the immune responses initiated by live bacteria, killed bacteria, bacterial supernatants, and purified bacterial components (26,31,32). Using live E. coli and S. aureus bacteria, we set up in vitro infection models that assessed the effects of these Gram-negative and Gram-positive bacteria on expression of IL-32, IL-6, and IL-8.…”
Section: Discussionmentioning
confidence: 99%
“…They produce various antimicrobial substances and inflammatory mediators that enhance effector functions of innate immunity and stimulate adaptive immunity, playing a pivotal role in the resolution of infection (27). A great number of studies dedicated to the analysis of the defensive response of MEC used killed bacteria or bacterial supernatants; however, those models have a significant limitation, since there is a great difference in the immune responses initiated by live bacteria, killed bacteria, bacterial supernatants, and purified bacterial components (26,31,32). Using live E. coli and S. aureus bacteria, we set up in vitro infection models that assessed the effects of these Gram-negative and Gram-positive bacteria on expression of IL-32, IL-6, and IL-8.…”
Section: Discussionmentioning
confidence: 99%
“…Among these receptors, expression of TLR2 and 4 substantially increased in quarters suffering from subclinical, moderate or severe infections, which correlated with severity of infection (Goldammer et al, 2004). TLR2 and TLR4 gene expression by mammary epithelial cells, monocytes-macrophages and neutrophyls has been reported (Gilbert et al, 2013;Strandberg et al, 2005;Wright et al, 1990); however, expression at the protein level remains to be documented. We performed IHC studies with antibodies to TLR2 and TLR4 to gain information on the localization of these receptors in bovine mammary tissue.…”
Section: Article In Pressmentioning
confidence: 99%
“…The results showed that C3G could decrease the levels of cholesterol in lipid rafts. Meanwhile, our cholesterol replenishment Mammary epithelial cells directly contact with the invading pathogens and play an important role in upper immunity ( 25 ). They recognize the pathogen-associated molecular patterns of invading pathogens via pattern recognition receptors such as TLRs, and induce the production of cytokines.…”
Section: Discussionmentioning
confidence: 99%